Reasons for medical consultation and causes of euthanasia of dogs in montevideo city (uruguay): a survey of veterinary practitioners. implications of behavioral problems (2012)
In Latin America there is little information about the frequent reasons of medical consultation and euthanasia in dogs, and the implications of behavior problems. Especially in Uruguay there isn’t information about it. The aim of this study was to know the most frequent reasons for medical consultation and euthanasia of dogs in Montevideo city through a survey of veterinary practitioners and the implications of behavioral problems. A survey to veterinary practitioners from one hundred (n = 100) randomly sampled veterinary clinics in the city of Montevideo was carried out. The most frequent reasons for medical consultation about dogs in veterinary practioners are consultations of skin affections, followed by digestive and respiratory affections, and less frequently infections, accidents and neoplasias (p and lt; 0.0001). The behavioral problems occupied only the 1% of the reasons for medical consultation in dogs. The most frequent reasons for euthanasia of dogs were by elderly dog and neoplasias, followed by kidney affections, infections and accidents (p and lt; 0.0001). Only 35% of veterinarians performed euthanasia for behavioral problems in their clinics. Among them, the euthanasia for behavior problems accounted for only 2%. Although euthanasia is carried out in Uruguay for behavior problems, it is so in a very low percentage.